A SURVEY ON RESPONSES OF COTTAGE, MICRO AND SMALL ENTERPRISES SECTOR DURING COVID-19 IN BANGLADESH - Rapti, Saila Sarmin; Sharmin, Eshrat; Hasan, Mehedi (International Journal of Small and Medium Enterprises, 2022)
This study examines the short-term impact of COVID-19 restrictions on small-sized enterprises based on phone and social media interviews. This research aimed to study Cottage, Micro, and Small Enterprises (CMSEs) during the covid-19 pandemic and analyze the policy measures taken afterwards. Affected by problems of logistics challenges, labour shortages, and drops in demand, most Small and Medium Enterprises (SMEs) were temporarily closed at the time of the first wave of covid-19 during our survey. We found several challenges encountered by the CMSEs owners during the early outbreak of Covid-19. This study used a descriptive analysis method of primary data obtained directly from field surveys and secondary data from Bangladesh Bank and SME foundation. This study focuses on the Dhaka city area during the Covid-19 pandemic. After reining in COVID-19, authorities eased lockdown restrictions in August 2020, and most of the small businesses had reopened by this time. Considering their issues and problems, the Government of Bangladesh and Bangladesh Bank have taken several policy measures to mitigate the loss of SME owners during the pandemic. These policies are also mentioned at the end of the study. JEL Classification Codes: A19, B10, B25, C10, C53.